PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - DEBORA DEBORA (E-Jurnal Akuntansi TSM, 2021)
The purpose of this research was to test the effect of Financial Performance to firm value of banking firm that listed at Indonesian Stock Exchange in the period of 2009-2013 either partially or simultaneously. This research used 95 samples from 19 firms in 5 years. The method used is panel data regression analysis with Generalized Method of Moments using EViews 7. This research using CAMEL analysis to assess the financial performance and using Price to Book Value to assess the firm value. From CAMEL analysis defined financial performance by using Loan to Deposit Ratio, Net Interest Margin, Return on Assets, Non Performing Loan, Net Profit Margin, and Capital Adequacy Ratio. The results showed that Loan to Deposit Ratio, Net Interest Margin, and Return on Assets partially has significant influence on the Price to Book Value,whether Non Performing Loan, Net Profit Margin, and Capital Adequacy Ratio partially has no significant influence on the Price to Book Value.